1971
DOI: 10.1351/pac197128040489
|View full text |Cite
|
Sign up to set email alerts
|

C-nucleosides: aspects of chemistry and mode of action

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Among structures containing N−N bonds, a key example is pyrazomycin (PZN, also known as pyrazofurin), a C ‐nucleoside containing an unusual pyrazole moiety . As a nucleoside analogue, PZN is a potent inhibitor of orotidine 5′‐monophosphate decarboxylase and possesses broad‐spectrum antiviral and antitumor activities . Early biosynthetic studies on PZN and its structural analogue formycin used isotope‐labeled precursors to establish that C‐3 to C‐6 of the pyrazole ring in PZN derive from C‐4 to C‐1 of glutamate or α‐ketoglutarate.…”
Section: Methodsmentioning
confidence: 99%
“…Among structures containing N−N bonds, a key example is pyrazomycin (PZN, also known as pyrazofurin), a C ‐nucleoside containing an unusual pyrazole moiety . As a nucleoside analogue, PZN is a potent inhibitor of orotidine 5′‐monophosphate decarboxylase and possesses broad‐spectrum antiviral and antitumor activities . Early biosynthetic studies on PZN and its structural analogue formycin used isotope‐labeled precursors to establish that C‐3 to C‐6 of the pyrazole ring in PZN derive from C‐4 to C‐1 of glutamate or α‐ketoglutarate.…”
Section: Methodsmentioning
confidence: 99%
“…However, since 5 did not undergo the Diels-Alder-reaction with one of the most reactive dienes, the Danishefsky diene, 11 we chose dimethyl [1,2,4,5]tetrazine-3,6-dicarboxylate 12 6a as one of the most activated electron-deficient heterocyclic diazadienes for [4+2]-cycloadditions with inverse electron demand. Reaction of 6a with the precursor 5 resulted in a typical cycloaddition-extrusion sequence (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…4 Although most naturally occurring C-glycosides are β-configured, some exist also as α-type. The antibiotic pyrazofurin anomer 1a has been isolated from Streptomyces candidus in 1969 by Gerzon et al 5 It has been suggested that pyrazofurin B (α-type) might be an artifact arising from acid-catalyzed isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…It is active against rhinovirus, and in this respect is more potent than ribavirin ). An excess of uridine in the culture medium abolished the antiviral effects, suggesting that the drug blocked steps in the metabolism of nucleotides (Gerzon et al, 1971). Pyrazofurin-5'-phosphate is an antagonist of uridine metabolism and blocks orotidylic deearboxylase (Shugar, 1974;Gutowski et al, 1975), but it also inhibits 5-amino-imidazole-4-carboxamide-l-fl-D-ribofuranosyl-5"-monophosphate (AICAR) formyltransferase, an enzyme involved in purine nucleotide biosynthesis.…”
Section: Pyrazofurin Ribavirin (Virazole) Selenazofurin and Bredininmentioning
confidence: 99%